REPRESENTASI ALPHA WOMAN: PERAN WANITA KARIR DALAM MENINGKATKAN EKONOMI KELUARGA - VERA RAHMAYANTI; Otong Karyono (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
This journal aims to describe the role of alpha women represented by career women in improving the family economy, and describe the pros and cons of career women in the family. This research uses the library research method. Alpha Woman is a popular term that has a global meaning and is often found in various social media. They are intelligent, confident and independent women. Nowadays, the spirit of women to become Alpha Woman is spreading rapidly. One phenomenon that occurs and is a representation of the alpha female spirit is the phenomenon of career women. However, this raises pros and cons, especially if they are married and have children. This is because there will be a double role of women as mothers, wives, workers and society. However, the existence of working women also brings many positive effects in various aspects, especially in terms of family economy, which helps to create family harmony. In creating family harmony, the roles and responsibilities of women cannot be separated from the roles and responsibilities of men. It requires understanding, commitment, openness, mutual respect and good cooperation between husband and wife.